Molecular Characterization and Antibiotic Resistance Profiling of Pleural Fluid Bacteria in Respiratory Infections - Abad, Ishraq Hasan; Mohsen, Zainab Abbas; Hussain, Amira Mohammad; Maryam Adnan Sahib (American Journal of Biology and Natural Sciences, 2025)
Background: Infective pleural effusion (IPE) is common and can have significant morbidity and mortality. Anaerobes have been associated with previously healthy patients and basinitis, both of which have an awaiting prognosis. However, confusion exists around identification and recommendations from Lunt et al. have been poorly applied. Methods: Gold standard presumptive cases of culture-proven IPE were identified from one institution between January 2011 to July 2018. Additional records were obtained for culture shapes in order to investigate the impact of laboratory processing. Clinical information was titrated from immunosuppression history and coastiologies reviewing discharge summaries and comorbid conditions. All analysis was undertaken using R. Dunn’s post-hoc tests were used to assess differences in age between groups. Results: 57 patients were identified, far outnumbering any other characteristical group. Median age was significantly younger than cohort (37.5 years, p < 0.001) and non-mixed cases were less common in malnourished patients (Odds Ratio = 0.026, p = 0.042). Conclusions: Anaerobes are most involved in UIP in younger patients with either feeding devices or a partner with poor oral control. With a median age of more than a decade lower than the wider cohort, early culture methods at the hospital either overlooked these agents or the majority failed to recognize them. Pleural infections, classed by the guidelines, are categorized into two of complicated effusion and empyema. The presence of both refers to the accumulation of any type of fluid in the pleural space causing illness, while an empyema is defined as the presence of pus within the visceral or parietal pleura resulting in a coalescing process leading to loculated effusions that can impair respiratory function and result in lung parenchyma destruction . This later statement is almost exclusively of bacterial origin with the organism’s ability to evade the host inflammatory response and scavenge iron from heme proteins marking its virulence involve. While the traditional approach is to culture for organism identification, this is notoriously difficult with high false-negative rates due to slow growth, earlier administration of antibiotics, or technical inability.